A forming method of composite aluminum material for deep drawing of refrigerator liner

Through the combination of segmented depth drawing and quick cooling technology, a thermal network structure is formed, which solves the problem of medium and high stress concentration in the deep drawing molding of the refrigerator inner liner, improves the thermal conductivity and mechanical strength of the aluminum alloy, and extends the service life.

CN118808429BActive Publication Date: 2025-01-07YUQIN PRECISION DRAWING TECH (SUZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411313124.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-07
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

During the process of deep drawing and forming of refrigerator inner liner, high-purity aluminum materials are easily deformed due to high stress concentration in a single forming stage, resulting in an increase in production costs and a decrease in finished product quality.

Method used

By using the composite aluminum molding method, the base material, thermally conductive reinforcement material and processing aid are mixed evenly and then melted under an inert atmosphere to form a molten aluminum alloy, and perform segmented deep drawing molding and combined with quick cooling technology, step by step The shape and thickness are adjusted and phosphating is performed to form a thermal network structure.

Benefits of technology

It reduces the degree of single-drawing deformation, reduces the internal stress and defects of aluminum alloy billets, maintains the consistency of thermal conductivity, improves the thermal conductivity, hardness and mechanical strength of the material, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118808429B_ABST
    Figure CN118808429B_ABST
Patent Text Reader

Abstract

The invention discloses a forming method of a composite aluminum material for deep drawing of a refrigerator liner, comprising: preparing an aluminum alloy, and preparing the refrigerator liner by combining a segmented deep drawing forming technology with a rapid cooling technology. The invention reduces the degree of single deep drawing deformation by segmented deep drawing of an aluminum alloy billet, thereby reducing the internal stress and defects of the aluminum alloy billet, helping to maintain the original structural integrity of the aluminum alloy billet, avoiding the destruction of the heat conduction path caused by rapid deformation, thereby maintaining the continuity of the heat conduction path, and further refining the grain structure of the material and reducing the residual stress by combining with the rapid cooling technology, thereby further improving the thermal conductivity of the material and significantly enhancing its hardness and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of deep drawing, and in particular to a forming method of a composite aluminum material for deep drawing of a refrigerator liner. Background Art

[0002] The refrigerator liner, i.e. the inner wall of the refrigerator, is an important structural part inside the refrigerator. It is located in the inner layer of the box (including the door), and its main function is to separate the refrigeration and freezing space from the insulation layer, and to store food through accessories such as ice trays, shelves and fruit and vegetable boxes. Deep drawing of the refrigerator liner, referred to as deep drawing or drawing, refers to the process of using a mold to stamp high-purity aluminum materials into refrigerator liner parts with an open hollow structure. This process combines sheet metal operations and metal forming technology, and the material is plastically deformed through the action of the mold to obtain the liner of the desired shape and size.

[0003] In the prior art, high-purity aluminum materials are usually directly deep-drawn to obtain refrigerator liner. During the direct deep-drawing process, since the material needs to undergo a large drawing in a single forming stage, high stress concentration is easily generated locally, causing the prepared liner to deform, resulting in an increase in production costs and a decrease in the quality of the finished product.

[0004] Therefore, it is necessary to design a forming method of a composite aluminum material for deep drawing of a refrigerator liner to solve the above problems. Summary of the invention

[0005] The invention overcomes the shortcomings of the prior art and provides a forming method of a composite aluminum material for deep drawing of a refrigerator liner.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a forming method of a composite aluminum material for deep drawing of a refrigerator liner, comprising the following steps:

[0007] Step S1, uniformly mixing the substrate, the thermal conductive reinforcing material, the reinforcing material and the processing aid, and melting the mixture under the protection of an inert atmosphere to obtain a molten aluminum alloy;

[0008] Step S2, pouring the molten aluminum alloy into a mold, air-cooling and solidifying it to form an ingot, and uniformly annealing the ingot;

[0009] Step S3, heating the obtained ingot, applying pressure to the ingot material for forging, so that the material is diverted, and adjusting it to a desired thickness and shape to obtain an aluminum alloy billet;

[0010] Step S4, heat-treating the aluminum alloy blank, and placing it in the first-stage drawing die for preliminary deformation, softening it and preliminarily fitting it to the shape of the die, completing pre-drawing, and rapidly cooling the aluminum alloy blank after pre-drawing to fix the shape of the aluminum alloy blank;

[0011] Step S5, phosphating the pre-drawn aluminum alloy billet, performing the heat treatment of step S4 on the phosphating aluminum alloy billet, and placing it in the second-stage drawing die, controlling the drawing amount, repeating the rapid cooling operation of step S4, and performing formal drawing forming on the basis of pre-drawing;

[0012] Step S6, perform the heat treatment of step S4 on the aluminum alloy billet after formal deep drawing, put it into the third stage drawing die, control the drawing amount, until the aluminum alloy billet forms a complete refrigerator liner, repeat the rapid cooling operation of step S4, and perform stress relief annealing on the refrigerator liner.

[0013] In a preferred embodiment of the present invention, in step S1, obtaining the aluminum alloy in a molten state comprises the following steps:

[0014] Step S11, selecting high-purity aluminum as a substrate, graphene powder as a thermal conductivity enhancing material, Al2O3 nanoparticles as a reinforcing material, and magnesium as a processing aid;

[0015] Step S12, adding the graphene powder to a mixed solvent of 0.5% polyethylene glycol and 99.5% ethanol, and ultrasonically treating for 25-30 minutes to uniformly disperse the graphene;

[0016] Step S13, immersing the Al2O3 nanoparticles in a dilute nitric acid solution, stirring for 25-30 minutes to remove the surface oxide layer and impurities, and washing with deionized water and drying to obtain pure Al2O3 nanoparticles;

[0017] Step S14: Under argon protection, high-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium are mixed and heated in a mass ratio of 88-98:0.5-2:2-5:1-5 until a molten aluminum alloy is obtained.

[0018] In a preferred embodiment of the present invention, in step S14, high-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium are mixed and heated to 650-750° C. to melt into a molten aluminum alloy.

[0019] In a preferred embodiment of the present invention, in step S2, the annealing treatment is performed by heating the ingot to 400-450°C and keeping the temperature for 2-2.5 hours to make the internal temperature of the ingot uniform, eliminating stress, and then naturally cooling the ingot to room temperature.

[0020] In a preferred embodiment of the present invention, in step S3, specifically, the ingot is heated to 400-450°C, and the heated ingot is gradually pressurized and forged in the range of 500-1500MPa until the ingot is adjusted to a range of 50%-70% of the original thickness.

[0021] In a preferred embodiment of the present invention, step S4 specifically includes the following sub-steps:

[0022] Step S41, placing the aluminum alloy billet in a high temperature furnace and heating it to 350°C, maintaining it for 30 minutes for preheating, and ensuring that the billet is heated evenly;

[0023] Step S42, continue heating to a target temperature of 400°C, keep the temperature stable, and continue heating for 2-4 hours;

[0024] Step S43, preheating the first-stage drawing die to 150-200° C., and applying lubricant on the surface of the first-stage drawing die;

[0025] Step S44, passing the heated aluminum alloy blank through a hydraulic drawing machine, drawing the aluminum alloy blank at a drawing speed of 10-20 mm / s and a drawing pressure of 500-800 MPa, until the deformation of the aluminum alloy blank reaches 20%-30%, thus completing the pre-drawing;

[0026] Step S45, taking out the aluminum alloy blank after pre-drawing, and using a liquid nitrogen nozzle to quickly cool the aluminum alloy blank to 20-25°C at a cooling rate of 80-125°C / s.

[0027] In a preferred embodiment of the present invention, in step S5, the pre-drawn aluminum alloy billet is subjected to phosphating treatment, which specifically includes the following steps:

[0028] Step S51, degreasing the pre-drawn aluminum alloy billet, specifically, placing it in a degreasing solution with a concentration of 3%-5%, at a temperature of 50-60° C., treating for 5-10 minutes to remove surface oil stains, and then washing with deionized water;

[0029] Step S52, pickling the aluminum alloy billet after the treatment in step S51, specifically, placing it in a dilute nitric acid solution with a concentration of 5%-10%, at a temperature of 20-30° C., for 3-5 minutes to remove the oxide layer and impurities, and then washing it with deionized water;

[0030] Step S53, put the aluminum alloy billet after degreasing and pickling into the phosphating tank, ensure that it is completely immersed, maintain the temperature of the phosphating solution at 65-70°C, and stir for 15 minutes to ensure that the phosphating film is evenly formed.

[0031] In a preferred embodiment of the present invention, the phosphating solution is a zinc dihydrogen phosphate solution with a concentration of 10-20 g / L.

[0032] In a preferred embodiment of the present invention, in step S5, the deformation amount of the aluminum alloy blank reaches 40%-50% through the second stage drawing die.

[0033] In a preferred embodiment of the present invention, in step S6, the deformation amount of the aluminum alloy blank reaches 60%-70% through the third stage drawing die.

[0034] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0035] (1) The present invention provides a forming method of a composite aluminum material for deep drawing of a refrigerator liner. By deep drawing an aluminum alloy billet in sections, the degree of single drawing deformation is reduced, thereby reducing the internal stress and defects of the aluminum alloy billet, helping to maintain the original structural integrity of the aluminum alloy billet, avoiding the destruction of the heat conduction path caused by rapid deformation, thereby maintaining the continuity of the heat conduction path, and by combining with the rapid cooling technology, the grain structure of the material is further refined, the residual stress is reduced, and the thermal conductivity of the material is further improved while also significantly enhancing its hardness and mechanical strength.

[0036] (2) In the preparation of aluminum alloys according to the present invention, graphene powder and Al2O3 nanoparticles are added and uniformly dispersed in the aluminum alloy, thereby forming a continuous heat conduction path inside the aluminum alloy and forming a heat conduction network structure, thereby improving the overall thermal conductivity while improving the structural strength of the aluminum alloy. Under the synergistic effect of graphene powder and Al2O3 nanoparticles, multi-scale heat conduction paths are formed, and the multi-scale heat conduction paths complement each other at different scales, further improving the thermal conductivity of the aluminum alloy.

[0037] (3) The addition of magnesium in the aluminum alloy prepared by the present invention can not only enhance the interfacial bonding force between the graphene powder and the high-purity aluminum, but also combine with the Al2O3 nanoparticles to enhance the dispersibility and stability of the graphene powder and the Al2O3 nanoparticles in the high-purity aluminum, thereby forming a continuous and efficient heat conduction path, greatly improving the overall thermal conductivity of the material. At the same time, magnesium can refine the grain structure of the high-purity aluminum and improve the overall uniformity and stability of the material.

[0038] (4) The present invention combines segmented drawing with rapid cooling technology to quickly cool the aluminum alloy material to fix its shape after each stage of drawing, thereby avoiding the accumulation of stress and deformation of the aluminum alloy material during multiple deformation processes, making the stress in each drawing stage evenly distributed and avoiding local stress concentration, thereby reducing the risk of cracks and fractures in the material and improving the overall strength and durability of the finished product.

[0039] (5) The present invention uses rapid cooling technology to quickly reduce the temperature of the aluminum alloy material, which can significantly refine the grain structure of the aluminum alloy material. The fine grains help reduce the resistance of grain boundaries to heat conduction, thereby improving the thermal conductivity of the material. At the same time, the rapid cooling technology helps to form a more uniform microstructure inside the material, reduce the structural inhomogeneity caused by uneven cooling rate, and further improve the overall performance of the material; it also helps to reduce residual austenite, increase the stability of the material, improve wear resistance and corrosion resistance, reduce internal stress, prevent deformation and cracking, and further improve the overall performance and service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0041] Figure 1 The present invention is a flow chart of a forming method of a composite aluminum material for deep drawing of a refrigerator liner. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0044] like Figure 1 As shown, a forming method of a composite aluminum material for deep drawing of a refrigerator liner comprises the following steps:

[0045] Step S1, uniformly mixing the substrate, the thermal conductive reinforcing material, the reinforcing material and the processing aid, and melting the mixture under the protection of an inert atmosphere to obtain a molten aluminum alloy;

[0046] Obtaining a molten aluminum alloy comprises the following steps:

[0047] Step S11, selecting high-purity aluminum as a substrate, graphene powder as a thermal conductivity enhancing material, Al2O3 nanoparticles as a reinforcing material, and magnesium as a processing aid;

[0048] Step S12, adding the graphene powder to a mixed solvent of 0.5% polyethylene glycol and 99.5% ethanol, and ultrasonically treating for 25-30 minutes to uniformly disperse the graphene;

[0049] Step S13, immersing the Al2O3 nanoparticles in a dilute nitric acid solution, stirring for 25-30 minutes to remove the surface oxide layer and impurities, and washing with deionized water and drying to obtain pure Al2O3 nanoparticles;

[0050] Step S14, under the protection of argon gas, high-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium are mixed in a mass ratio of 88-98:0.5-2:2-5:1-5 and heated to 650-750°C until the high-purity aluminum and magnesium are in a molten state to form a molten aluminum alloy, wherein the high-purity aluminum is specifically 1050 type aluminum.

[0051] Graphene powder has extremely high thermal conductivity and mechanical strength, which can significantly improve the thermal conductivity of aluminum alloys. Al2O3 nanoparticles can increase the hardness and strength of aluminum alloys, while improving their wear resistance and corrosion resistance.

[0052] In the process of preparing the aluminum alloy, a 0.5% polyethylene glycol solution and a 99.5% ethanol solution are mixed, and graphene powder is added to the mixed solvent, and ultrasonic treatment is performed for 25-30 minutes to make the graphene powders evenly dispersed, ensure the uniform distribution of the graphene powders in the high-purity aluminum matrix, and improve its thermal conductivity and mechanical properties;

[0053] The Al2O3 nanoparticles are immersed in a dilute nitric acid solution with a concentration of 5%-10%, and stirred for 25-30 minutes to remove the oxide layer and impurities on the surface of the Al2O3 nanoparticles to ensure the cleanliness of the surface of the Al2O3 nanoparticles. Subsequently, the Al2O3 nanoparticles are washed with deionized water and dried to ensure the purity of the particles, while improving the dispersibility and enhancement effect of the Al2O3 nanoparticles;

[0054] In order to reduce the oxidation of high-purity aluminum and Al2O3 nanoparticles, it is necessary to carry out smelting and casting under an inert atmosphere (argon), by mixing high-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium in a mass ratio of 88-98:0.5-2:2-5:1-5 and heating to 650-750°C, so that the high-purity aluminum and magnesium are in a molten state, and the graphene powder and Al2O3 nanoparticles are evenly distributed in the molten high-purity aluminum and magnesium to form a molten aluminum alloy;

[0055] For the aluminum alloy prepared as above, by adding graphene powder and Al2O3 nanoparticles and uniformly dispersing them in the aluminum alloy, a continuous heat conduction path is formed inside the aluminum alloy, and a heat conduction network structure is formed, thereby improving the overall thermal conductivity while improving the structural strength of the aluminum alloy, and under the synergistic effect of graphene powder and Al2O3 nanoparticles, a multi-scale heat conduction path is formed, and the multi-scale heat conduction paths complement each other at different scales, further improving the thermal conductivity of the aluminum alloy;

[0056] The addition of magnesium can not only enhance the interfacial bonding force between graphene powder and high-purity aluminum, but also combine with Al2O3 nanoparticles to enhance the dispersion and stability of graphene powder and Al2O3 nanoparticles in high-purity aluminum, forming a continuous and efficient thermal conduction path, greatly improving the overall thermal conductivity of the material. At the same time, magnesium can refine the grain structure of high-purity aluminum and improve the overall uniformity and stability of the material.

[0057] Step S2, pouring the molten aluminum alloy into a mold, air-cooling and solidifying it to form an ingot, and uniformly annealing the ingot;

[0058] The specific operation of step S2 is to pour the molten aluminum alloy into a pre-prepared mold, and solidify the molten aluminum alloy in the mold by air cooling. The solidification mainly converts the liquid alloy into a solid ingot to initially form a macroscopic form of the material, wherein the thickness of the ingot is within the range of 1.5 mm ± 2.5 mm, the length is 800 mm ± 5 mm, and the width is 500 mm ± 5 mm;

[0059] Annealing treatment, specifically, heating the ingot to 400-450℃, keeping it warm for 2-2.5h to make the internal temperature of the ingot uniform, eliminating stress, and then naturally cooling it to room temperature, which improves the plasticity and ductility of the ingot and facilitates the subsequent multi-stage segmented drawing operation; through solidification and annealing treatment, an ingot with uniform structure and low internal stress is formed, providing a stable foundation for subsequent forging and drawing operations.

[0060] Step S3, heating the obtained ingot, applying pressure to the ingot material for forging, so that the material is diverted, and adjusting it to a desired thickness and shape to obtain an aluminum alloy billet;

[0061] Specifically, the ingot is heated to 400-450°C to soften the internal structure of the ingot evenly to facilitate subsequent forging operations, and the heated ingot is gradually pressurized within the range of 500-1500MPa for forging, wherein the gradual pressure can ensure uniform deformation of the ingot and avoid stress concentration and cracking until the ingot is adjusted to 50%-70% of the original thickness.

[0062] Step S4, heat-treating the aluminum alloy blank, and placing it in the first-stage drawing die for preliminary deformation, softening it and preliminarily fitting it to the shape of the die, completing pre-drawing, and rapidly cooling the aluminum alloy blank after pre-drawing to fix the shape of the aluminum alloy blank;

[0063] It includes the following sub-steps:

[0064] Step S41, placing the aluminum alloy billet in a high temperature furnace and heating it to 350°C, maintaining it for 30 minutes for preheating, and ensuring that the billet is heated evenly;

[0065] Step S42, continue heating to a target temperature of 400°C, keep the temperature stable, and continue heating for 2-4 hours;

[0066] Step S43, preheating the first-stage drawing die to 150-200° C., and applying lubricant on the surface of the first-stage drawing die;

[0067] Step S44, passing the heated aluminum alloy blank through a hydraulic drawing machine, drawing the aluminum alloy blank at a drawing speed of 10-20 mm / s and a drawing pressure of 500-800 MPa, until the deformation of the aluminum alloy blank reaches 20%-30%, thus completing the pre-drawing;

[0068] Step S45, taking out the aluminum alloy blank after pre-drawing, and using a liquid nitrogen nozzle to quickly cool the aluminum alloy blank to 20-25°C at a cooling rate of 80-125°C / s.

[0069] Step S5, phosphating the pre-drawn aluminum alloy billet, performing the heat treatment of step S4 on the phosphating aluminum alloy billet, and placing it in the second-stage drawing die, controlling the drawing amount, repeating the rapid cooling operation of step S4, and performing formal drawing forming on the basis of pre-drawing;

[0070] Step S6, perform the heat treatment of step S4 on the aluminum alloy billet after formal deep drawing, put it into the third stage drawing die, control the drawing amount, until the aluminum alloy billet forms a complete refrigerator liner, repeat the rapid cooling operation of step S4, and perform stress relief annealing on the refrigerator liner.

[0071] Through steps S4, S5, and S6, the aluminum alloy billet is subjected to multi-stage deep drawing, which reduces the degree of single deep drawing deformation, thereby reducing the internal stress and defects of the aluminum alloy billet, helping to maintain the original structural integrity of the aluminum alloy billet, avoiding the destruction of the heat conduction path due to rapid deformation, thereby maintaining the continuity of the heat conduction path, and performing rapid cooling treatment after each stage of deep drawing of the aluminum alloy billet, thereby avoiding the accumulation of stress and deformation of the aluminum alloy material during multiple deformation processes, making the stress in each deep drawing stage evenly distributed, avoiding local stress concentration, thereby reducing the risk of cracks and fractures of the material, and improving the overall strength and durability of the finished product.

[0072] The pre-drawn aluminum alloy billet is subjected to phosphating treatment, which specifically includes the following steps:

[0073] Step S51, degreasing the pre-drawn aluminum alloy billet, specifically, placing it in a degreasing solution with a concentration of 3%-5%, at a temperature of 50-60° C., treating for 5-10 minutes to remove surface oil stains, and then washing with deionized water;

[0074] Step S52, pickling the aluminum alloy billet after the treatment in step S51, specifically, placing it in a dilute nitric acid solution with a concentration of 5%-10%, at a temperature of 20-30° C., for 3-5 minutes to remove the oxide layer and impurities, and then washing it with deionized water;

[0075] Step S53, put the aluminum alloy billet after degreasing and pickling into the phosphating tank, ensure that it is completely immersed, maintain the temperature of the phosphating solution at 65-70°C, and stir for 15 minutes to ensure that the phosphating film is evenly formed.

[0076] In the present invention, the phosphating solution is a zinc dihydrogen phosphate solution with a concentration of 10-20 g / L.

[0077] In the present invention, in the step S5, the deformation amount of the aluminum alloy blank reaches 40%-50% through the second stage drawing die.

[0078] In the present invention, in step S6, the deformation amount of the aluminum alloy blank reaches 60%-70% through the third stage drawing die.

[0079] Aluminum plates are mostly used in the preparation of refrigerator liner on the market. The following experiment was conducted to compare the performance of the aluminum alloy obtained by different raw material ratios in the preparation of refrigerator liner in the present invention with that of aluminum plates.

[0080] Experimental example:

[0081] (I) Experimental purpose

[0082] 1. Investigate the effects of different proportions of substrate, thermal conductivity enhancing material, reinforcing material and processing aid on the performance of composite aluminum alloy.

[0083] 2. Compare the differences in key properties (such as thermal conductivity, strength, and corrosion resistance) between composite aluminum alloys and traditional aluminum sheets.

[0084] (II) Detection method

[0085] Thermal conductivity test: Use a laser thermal conductivity meter to measure the thermal conductivity of aluminum alloys with different ratios and record the thermal conductivity values.

[0086] Tensile performance test: Use an electronic universal testing machine to test the tensile strength and elongation of aluminum alloys with different proportions.

[0087] Hardness test: Use Vickers hardness tester to measure the hardness values ​​of aluminum alloys with different proportions.

[0088] Microstructure analysis: A scanning electron microscope (SEM) was used to observe the microstructure of aluminum alloys with different proportions, and the distribution of graphene powder and Al2O3 nanoparticles was analyzed. The results were divided into three levels, where level 1 indicates uniform distribution, level 2 indicates slight agglomeration and relatively uniform particle distribution, and level 3 indicates obvious agglomeration and uneven distribution.

[0089] (III) Experimental preparation

[0090] Prepare multiple groups of experimental samples, each group is mixed in different proportions to prepare aluminum alloys, among which,

[0091] Experimental group 1: High-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium were mixed in a mass ratio of 90:0.5:2:1 and heated to 700°C until the high-purity aluminum and magnesium were molten to form a molten aluminum alloy;

[0092] Experimental group 2: High-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium were mixed in a mass ratio of 90:0.5:3:1 and heated to 700°C until the high-purity aluminum and magnesium were molten to form a molten aluminum alloy;

[0093] Experimental group 3: High-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium were mixed in a mass ratio of 90:0.5:4:1 and heated to 700°C until the high-purity aluminum and magnesium were molten to form a molten aluminum alloy;

[0094] Experimental group 4: High-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium were mixed in a mass ratio of 90:0.5:5:1 and heated to 700°C until the high-purity aluminum and magnesium were molten to form a molten aluminum alloy;

[0095] Experimental group 5: High-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium were mixed in a mass ratio of 90:1:3:1 and heated to 700°C until the high-purity aluminum and magnesium were molten to form a molten aluminum alloy;

[0096] Experimental group 6: High-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium were mixed in a mass ratio of 90:1.5:3:1 and heated to 700°C until the high-purity aluminum and magnesium were molten to form a molten aluminum alloy;

[0097] Experimental group 7: High-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium were mixed in a mass ratio of 90:2:3:1 and heated to 700°C until the high-purity aluminum and magnesium were molten to form a molten aluminum alloy;

[0098] Experimental group 8: High-purity aluminum, graphene powder, and Al2O3 nanoparticles were mixed in a mass ratio of 90:1.5:3 and heated to 700°C until the high-purity aluminum was molten to form a molten aluminum alloy;

[0099] Control group: High-purity aluminum was selected and heated to 700°C until the high-purity aluminum was in a molten state, forming a molten state.

[0100] The materials obtained from the experimental groups 1-8 and the control group were poured into a mold, air-cooled and solidified to form an ingot-like aluminum alloy, and uniformly annealed, and the obtained aluminum alloy was subjected to a performance test experiment, as shown in Table 1;

[0101] Table 1

[0102]

[0103] By comparing experimental groups 1-4, it can be concluded that as the proportion of Al2O3 nanoparticles increases, the tensile strength and hardness of the aluminum alloy are improved, and the Al2O3 nanoparticles are evenly distributed inside the aluminum alloy. However, as the proportion of Al2O3 nanoparticles is too large, its thermal conductivity decreases, and the uniformity of the distribution of Al2O3 nanoparticles inside the aluminum alloy decreases. This is mainly because as the proportion of Al2O3 nanoparticles increases, the interface area between them and the aluminum matrix increases, and there will be a certain thermal resistance at each interface. The interface thermal resistance will be superimposed, which significantly affects the overall thermal conductivity of the material. In addition, Al2O3 nanoparticles have strong surface energy and interaction force. When their proportion increases, it is easier for particles to agglomerate. Although magnesium can improve the interfacial bonding force between particles and the matrix, when the number of particles increases significantly, the agglomeration effect becomes more significant, and the dispersion effect of magnesium is difficult to offset this trend. Therefore, experimental group 2 is the optimal solution among experimental groups 1-4;

[0104] By comparing experimental groups 5-8, it can be concluded that by increasing the proportion of graphene powder, the graphene powder and Al2O3 nanoparticles are evenly distributed inside the aluminum alloy, which can significantly improve thermal conductivity, tensile strength, ductility, and hardness. This is mainly because graphene can form an efficient thermal conduction path inside the matrix and form a thermal conduction network structure to effectively conduct heat. In addition, the interface bonding force between graphene and the aluminum matrix is ​​strong, which further reduces the interface thermal resistance and improves the overall thermal conductivity and ductility. Moreover, because the network structure is formed, the external force can be effectively dispersed, and the deformation resistance of the composite material can be improved, thereby improving the tensile strength and hardness.

[0105] However, if the proportion of graphene powder is too large, its thermal conductivity, tensile strength, ductility and hardness will decrease. Graphene has a high specific surface area and strong van der Waals force, so it is easy to agglomerate. Magnesium mainly improves dispersibility and stability by bonding with the interface between graphene powder and Al2O3 nanoparticles. When the ratio of graphene powder to Al2O3 nanoparticles is too high, the interface bonding ability of magnesium may reach saturation and the dispersion effect cannot be further improved. The dispersion effect of magnesium will be limited. After agglomeration occurs, a large number of interfaces will be formed inside the agglomerates. Thermal resistance leads to reduced heat transfer efficiency. The presence of agglomerates destroys the original continuous heat conduction path of graphene, thereby reducing the thermal conductivity of the overall material. The presence of agglomerates will lead to stress concentration inside the material, especially when subjected to stress. The agglomerates become stress concentration points, which can easily cause crack propagation and material damage, thereby reducing the tensile strength. Since agglomerates are brittle phases, their presence can easily cause the material to break prematurely during the strain process, reducing the ductility of the material. Based on this, by comparing experimental group 6 and the control group, it can be concluded that experimental group 6 is the optimal solution for the aluminum alloy in the present invention.

[0106] The obtained aluminum alloy is subjected to segmented deep drawing combined with rapid cooling treatment, and the following operations are performed;

[0107] Embodiment 1:

[0108] The ingot-shaped aluminum alloy is heated to 450°C, and forged gradually under a pressure of 800MPa until the ingot is adjusted to a range of 50%-70% of the original thickness. The aluminum alloy billet is placed in a high-temperature furnace and heated to 350°C, and maintained for 30 minutes for preheating to ensure that the billet is evenly heated, and then continued to heat to a target temperature of 400°C, and the temperature is kept stable, and the heating is continued for 2.5 hours. The first-stage drawing die is preheated to 180°C, and lubricant is applied to the surface of the first-stage drawing die. The heated aluminum alloy billet is passed through a hydraulic drawing machine at a drawing speed of 15mm / s and a drawing pressure of 600MPa to draw the aluminum alloy billet until the deformation of the aluminum alloy billet reaches 20%-30%, and the pre-drawing is completed. The aluminum alloy billet after pre-drawing is taken out, and the aluminum alloy billet is quickly cooled to 20-25°C at a cooling rate of 105°C / s using a liquid nitrogen nozzle;

[0109] The pre-drawn aluminum alloy billet is placed into the drawing die of the second stage, the drawing amount is controlled, and the deformation of the aluminum alloy billet reaches 40%-50%. The operation of step S4 is repeated, and formal drawing is performed on the basis of pre-drawing; the aluminum alloy billet after formal drawing is placed into the drawing die of the third stage, the drawing amount is controlled, and the deformation of the aluminum alloy billet reaches 60%-70%. The operation of step S5 is repeated iteratively, and the drawing amount is controlled until the aluminum alloy billet forms a complete refrigerator liner, and the refrigerator liner is subjected to stress relief annealing.

[0110] Embodiment 2:

[0111] The ingot-style aluminum alloy is heated to 450°C, and forged gradually under a pressure of 800MPa until the ingot is adjusted to a range of 50%-70% of the original thickness. The aluminum alloy billet is placed in a high-temperature furnace and heated to 350°C, maintained for 30 minutes for preheating to ensure uniform heating of the billet, and continued to heat to a target temperature of 400°C, maintaining a stable temperature, and continuously heating for 2.5 hours. The completed drawing die is preheated to 180°C, and lubricant is applied to the surface of the first-stage drawing die. The heated aluminum alloy billet is passed through a hydraulic drawing machine at a drawing speed of 15mm / s and a drawing pressure of 600MPa to draw the aluminum alloy billet until the refrigerator liner is formed and the drawing is completed. The aluminum alloy billet after pre-drawing is taken out, and a liquid nitrogen nozzle is used to quickly cool the aluminum alloy billet to 20-25°C at a cooling rate of 105°C / s.

[0112] Through Example 1 and Example 2, the segmented deep drawing + rapid cooling technology is verified. Compared with the residual stress change of the refrigerator liner obtained by traditional direct deep drawing, the surface of the sample is measured using an X-ray diffractometer;

[0113] As shown in Table 2, the refrigerator liner performance test data obtained in Example 1 and Example 2

[0114] Table 2

[0115] Performance Indicators Segmented deep drawing + rapid cooling technology Traditional direct drawing Thermal conductivity (W / mK) 268 242 Tensile strength(MPa) 179.5 98.6 Ductility(%) 22.7 21.2 Hardness (HV) 71 20 Residual stress (MPa) 18.5 53.6

[0116] By comparing Example 1 and Example 2, it can be concluded that the segmented deep drawing combined with the rapid cooling technology can significantly improve the stress in the forming of the refrigerator liner, and at the same time, improve the thermal conductivity of the refrigerator liner, mainly because the degree of single deep drawing deformation is reduced by segmented deep drawing of the aluminum alloy billet, thereby reducing the internal stress and defects of the aluminum alloy billet, which helps to maintain the original structural integrity of the aluminum alloy billet, avoid the destruction of the heat conduction path caused by rapid deformation, and thus maintain the continuity of the heat conduction path;

[0117] Rapidly lowering the temperature of aluminum alloy materials can significantly refine the grain structure of aluminum alloy materials. Fine grains help reduce the barrier of grain boundaries to heat conduction, thereby improving the thermal conductivity of the material. At the same time, rapid cooling technology helps to form a more uniform microstructure inside the material, reduce the structural inhomogeneity caused by uneven cooling rate, and further improve the overall performance of the material; it also helps to reduce residual austenite, increase the stability of the material, improve wear resistance and corrosion resistance, reduce internal stress, prevent deformation and cracking, and further improve the overall performance and service life of the material;

[0118] The combination of segmented deep drawing and rapid cooling technology effectively reduces stress accumulation. The rapid cooling after each deep drawing helps to reduce residual stress and reduce material deformation. At the same time, it further refines the grain structure of the material, reduces residual stress, and further improves the thermal conductivity of the material while significantly enhancing its hardness and mechanical strength.

[0119] In summary, the aluminum alloy prepared by the graphene powder, Al2O3 nanoparticles and magnesium material used in the present invention and high-purity aluminum can significantly improve the fluidity of the aluminum alloy, because graphene has excellent lubrication properties, and the addition of magnesium can improve the fluidity of the aluminum alloy, prevent the material from having excessive resistance during the drawing process, and optimize the fluidity to help evenly distribute the pressure at each drawing stage, reduce stress concentration and defects inside the material, and thus obtain higher quality molded parts; magnesium can refine the grain structure of the aluminum, and the refined grain structure can effectively reduce local stress and deformation risks, so that the material exhibits better forming ability and uniformity at each stage. Therefore, by combining the aluminum alloy with segmented drawing and rapid cooling technology, the prepared refrigerator liner can have high thermal conductivity and low stress.

[0120] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A method for forming a composite aluminum material for deep drawing of a refrigerator liner, characterized in that: The following steps are involved: Step S1, uniformly mixing the substrate, the thermal conductive reinforcing material, the reinforcing material and the processing aid, and melting the mixture under the protection of an inert atmosphere to obtain a molten aluminum alloy; The specific steps include: Step S11, selecting high-purity aluminum as a substrate, graphene powder as a thermal conductivity enhancing material, Al2O3 nanoparticles as a reinforcing material, and magnesium as a processing aid; Step S12, adding the graphene powder to a mixed solvent of 0.5% polyethylene glycol and 99.5% ethanol, and ultrasonically treating for 25-30 minutes to uniformly disperse the graphene; Step S13, immersing the Al2O3 nanoparticles in a dilute nitric acid solution, stirring for 25-30 minutes to remove the surface oxide layer and impurities, and washing with deionized water and drying to obtain pure Al2O3 nanoparticles; Step S14, under the protection of argon gas, high-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium are mixed and heated in a mass ratio of 88-98:0.5-2:2-5:1-5 until a molten aluminum alloy is obtained; Step S2, pouring the molten aluminum alloy into a mold, air-cooling and solidifying it to form an ingot, and uniformly annealing the ingot; Step S3, heating the obtained ingot, applying pressure to the ingot material for forging, so that the material is diverted, and adjusting it to a desired thickness and shape to obtain an aluminum alloy billet; Step S4, heat-treating the aluminum alloy blank, and placing it in the first-stage drawing die for preliminary deformation, softening it and preliminarily fitting it to the shape of the die, completing pre-drawing, and rapidly cooling the aluminum alloy blank after pre-drawing to fix the shape of the aluminum alloy blank; It includes the following sub-steps: Step S41, placing the aluminum alloy billet in a high temperature furnace and heating it to 350° C., maintaining it for 30 minutes for preheating, and ensuring that the aluminum alloy billet is heated evenly; Step S42, continue heating to a target temperature of 400°C, keep the temperature stable, and continue heating for 2-4 hours; Step S43, preheating the first-stage drawing die to 150-200° C., and applying lubricant on the surface of the first-stage drawing die; Step S44, passing the heated aluminum alloy blank through a hydraulic drawing machine, drawing the aluminum alloy blank at a drawing speed of 10-20 mm / s and a drawing pressure of 500-800 MPa, until the deformation of the aluminum alloy blank reaches 20%-30%, thereby completing the pre-drawing; Step S45, taking out the aluminum alloy blank after pre-drawing, and using a liquid nitrogen nozzle to quickly cool the aluminum alloy blank to 20-25°C at a cooling rate of 80-125°C / s; Step S5, phosphating the pre-drawn aluminum alloy billet, performing the heat treatment of step S4 on the phosphating aluminum alloy billet, and placing it in the second-stage drawing die, controlling the drawing amount, repeating the rapid cooling operation of step S4, and performing formal drawing forming on the basis of pre-drawing; Step S6, perform the heat treatment of step S4 on the aluminum alloy billet after formal deep drawing, put it into the third stage drawing die, control the drawing amount, until the aluminum alloy billet forms a complete refrigerator liner, repeat the rapid cooling operation of step S4, and perform stress relief annealing on the refrigerator liner.

2. The forming method of a composite aluminum material for deep drawing of a refrigerator liner according to claim 1, characterized in that: In step S14, high-purity aluminum, graphene powder, Al2O3 nanoparticles, and magnesium are mixed and heated to 650-750° C. to melt into a molten aluminum alloy.

3. The forming method of a composite aluminum material for deep drawing of a refrigerator liner according to claim 1, characterized in that: In step S2, the ingot is subjected to annealing treatment, specifically, the temperature of the ingot is raised to 400-450°C, and the temperature is kept for 2-2.5 hours to make the temperature inside the ingot uniform. After eliminating the stress, the ingot is naturally cooled to room temperature.

4. The method for forming a composite aluminum material for deep drawing of a refrigerator liner according to claim 1, characterized in that: In the step S3, specifically, the ingot is heated to 400-450°C, and the heated ingot is gradually pressed and forged within the range of 500-1500 MPa until the ingot is adjusted to a range of 50%-70% of the original thickness.

5. The method for forming a composite aluminum material for deep drawing of a refrigerator liner according to claim 1, characterized in that: In step S5, the pre-drawn aluminum alloy blank is subjected to phosphating treatment, which specifically includes the following steps: Step S51, degreasing the pre-drawn aluminum alloy billet, specifically, placing it in a degreasing solution with a concentration of 3%-5%, at a temperature of 50-60° C., treating for 5-10 minutes to remove surface oil stains, and then washing with deionized water; Step S52, pickling the aluminum alloy billet after the treatment in step S51, specifically, placing it in a dilute nitric acid solution with a concentration of 5%-10%, at a temperature of 20-30° C., for 3-5 minutes to remove the oxide layer and impurities, and then washing it with deionized water; Step S53, put the aluminum alloy billet after degreasing and pickling into the phosphating tank, ensure that it is completely immersed, maintain the temperature of the phosphating solution at 65-70°C, and stir for 15 minutes to ensure that the phosphating film is evenly formed.

6. The method for forming a composite aluminum material for deep drawing of a refrigerator liner according to claim 5, characterized in that: The phosphating solution is a zinc dihydrogen phosphate solution with a concentration of 10-20 g / L.

7. The method for forming a composite aluminum material for deep drawing of a refrigerator liner according to claim 1, characterized in that: In step S5, the deformation amount of the aluminum alloy blank reaches 40%-50% through the second stage drawing die.

8. The method for forming a composite aluminum material for deep drawing of a refrigerator liner according to claim 1, characterized in that: In step S6, the deformation amount of the aluminum alloy blank reaches 60%-70% through the third stage drawing die.

Citation Information

Patent Citations

  • Weldless water heater liner processing technique, water heater liner and water heater

    CN110125612A

  • Pressure container aluminum liner drawing method

    CN110538923A